2018
DOI: 10.31234/osf.io/yx8m4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for a dissociation between causal beliefs and instrumental actions

Abstract: Human experiments have demonstrated that instrumental performance of an action and the causal beliefs of the effectiveness of an action in producing a reward are correlated and controlled by the probability of an action leading to a reward. The animal literature, however, shows that instrumental performance under free-operant training differs even when these reward probabilities are matched while subjects undergo training under ratio or interval schedules of reward. In two experiments, we investigated whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This prediction is clearly at variance with the empirical evidence showing a sustained ratio-interval performance effect with extended training (e.g. Catania et al, 1977;Pérez et al, 2016;Pérez and Soto, 2020). We have already noted that interval schedules differentially reinforce long IRTs-the longer an agent waits before responding again, the more likely it is that a further outcome has become available with the resultant increase in the probability of reinforcement (see Figure 2a).…”
Section: Performance After Extended Trainingsupporting
confidence: 54%
See 2 more Smart Citations
“…This prediction is clearly at variance with the empirical evidence showing a sustained ratio-interval performance effect with extended training (e.g. Catania et al, 1977;Pérez et al, 2016;Pérez and Soto, 2020). We have already noted that interval schedules differentially reinforce long IRTs-the longer an agent waits before responding again, the more likely it is that a further outcome has become available with the resultant increase in the probability of reinforcement (see Figure 2a).…”
Section: Performance After Extended Trainingsupporting
confidence: 54%
“…As the interval-trained rats pressed at a lower rate than the ratiotrained animals, goal-directed control was observed in the ratio-trained group even under a lower outcome probability experienced by those rats. The higher levels of performance produced by ratio training under matched reward probabilities (Catania et al, 1977;Pérez et al, 2016;Pérez and Soto, 2020) and the impact of the training schedule on the outcome devaluation effect (see Gremel and Costa, 2013;Hilario et al, 2012;Wiltgen et al, 2012) have now received extensive replication.…”
Section: Ratio and Interval Contingenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the reward rate sets an average interval between each available reward and so variations response rate do not generally produce variations in outcome rate-the reward rate is fixed at the scheduled interval between rewards once the response rate is sufficiently high to collect all rewards. Consistent with this idea, a wealth of data have demonstrated that RR schedules generate higher response rates than RI schedules even when the reward probability HUMAN INSTRUMENTAL BEHAVIOR 4 (Pérez and Soto, 2020) or reward rate (Reed, 2001) is matched between the two conditions.…”
Section: Introductionmentioning
confidence: 90%
“…It is now well established that these schedules can affect whether behavior is goal-directed or habitual. More precisely, the evidence suggests that the molar aspects of behavior seem to be considered by people when deciding to act on the environment in a goal-directed manner and that the molecular aspects are more important for behaving habitually (Perez & Dickinson, 2020;Pérez & Soto, 2020). So far, I know of no experiment in which molar and molecular aspects are encouraged by experimental manipulations, but it is likely that they will also play a role in how observers ascribe causality to actions and therefore imitate (copy actions) or emulate (copy intentions to obtain a goal).…”
Section: Action Sequences Habits and Attention In Copying Strategiesmentioning
confidence: 99%